Pengaruh Kepemimpinan Pendidikan Islam terhadap Pengembangan Kepemimpinan dan Pola Asuh Orang Tua dalam Menanamkan Kepribadian Anak Keluarga TNI (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2022)
Research focuses on Islamic educational leadership influencing the leadership development and parenting of parents who are members of the military (TNI) in instilling children's personalities, because parental parenting is also related to the way parents provide education to their children. This research is a qualitative-descriptive type. Data accumulation techniques by means of in-depth interviews. From the results of the study, it was found that Islamic education leadership has an influence that underlies leadership development inspired by the ideal leadership of the Prophet as a maksum commander,Islamic education leadership also affects the implied parenting, namely democratic, and militaristic parenting. By applying these democratic parenting styles, religious, theoretical, and social personalities are formed in children.